No Free Lunch? Welfare Analysis of Firms Selling Through Expert Intermediaries - Grennan, Matthew; Myers, Kyle R; Swanson, Ashley; Chatterji, Aaron (Review of Economic Studies, 2025)
Abstract We study how firms target and influence expert intermediaries. In our context, pharmaceutical manufacturers provide payments to physicians during promotional interactions. We develop an identification strategy based on plausibly exogenous variation in payments driven by differential exposure to spillovers from AMC CoI policies. Using a case study of an important class of cardiovascular drugs, we estimate heterogeneous effects of payments on prescribing, with firms targeting highly responsive physicians. We also develop a model of supply and demand, which allows us to quantify how oligopoly prices reduce drug prescribing, and how payments move prescribing closer to the optimal level, but at great financial cost. In our estimated model, whether consumers are harmed by payments depends on whether there is substantial under-prescribing due to behavioural or other frictions. In a final exercise, we calibrate such frictions using clinical data and estimate that payments benefit consumers in this case study.